Secure Multi-keyword Similarity Search Over Encrypted Data With Security Improvement - Mohammed, Hussein M.; Abdulsada, Ayad I. (Iraqi Journal for Electrical and Electronic Engineering, 2021)
Searchable encryption (SE) is an interesting tool that enables clients to outsource their encrypted data into external cloud servers with unlimited storage and computing power and gives them the ability to search their data without decryption. The current solutions of SE support single-